Kinerja Ombudsman RI Perwakilan Provinsi Bengkulu dalam Meningkatkan Kualitas Pelayanan Publik Di Kota Bengkulu - Billy Ramadhan; Harmiati Harmiati; Heru Purnawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Public service is a fundamental activity that constitutes one of the main duties of the government in administering governance. The Indonesian Ombudsman is a state institution with the authority to oversee the implementation of public services, both those provided by state organizers. One of the tasks of the Indonesian Ombudsman Representative in Bengkulu Province is to prevent maladministration in public services in the Bengkulu region. This research aims to understand the performance of the Indonesian Ombudsman Representative in Bengkulu Province in preventing maladministration in public services, particularly in Bengkulu City, to improve the quality of public services. The study employs a descriptive qualitative approach. The analysis is conducted using the performance measurement theory proposed by Agus Dwiyanto (2006), which includes productivity, service quality, responsiveness, responsibility, and accountability. The data for this research were obtained from interviews, observations, and documentation. The results indicate that the performance of the Indonesian Ombudsman Representative in Bengkulu Province in preventing maladministration in public services in 2024 is already optimal. This is evidenced by the recapitulation data of compliance assessments for the implementation of public services by local governments in 2024, where the Bengkulu City government falls into category A with a final score of 90.74 and has met 5 out of 5 indicators proposed by Agus Dwiyanto (2006).